From a Non-Integrated Territory to a Metropolitan Park The West Area of Santa Fe (Argentina) - Mirta Soijet; Yanina Uriarte (Department of Architecture Universitas Muhammadiyah Jakarta, 2017)
This paper presents and describes the city of Santa Fe (Argentina) and specially the west area characterized by the dominant presence of water. The evolution of that city establishes a constant battle to